2011
DOI: 10.1111/j.1469-8986.2011.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

The feedback‐related negativity (FRN) in adolescents

Abstract: This study examined age-related differences in the ERP correlates of external feedback processing (i.e., the feedback-related negativity [FRN]) in adolescent and young adult males, using a simple gambling task involving unpredictable monetary losses and gains of low and high magnitude. The FRN was larger after losses than gains, and was modulated by the magnitude of gains, but not the magnitude of losses, for all participants regardless of age. FRN amplitude was larger in adolescents than adults and also discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 53 publications
(106 reference statements)
7
48
0
Order By: Relevance
“…Participants were screened for any visual, neurological or psychological disorders prior to enrollment in the study. Data from 10 of the boys (selected to provide an age-matched sample with girls) were previously reported in a study with an all-male sample [28]. Data from 3 participants were discarded due to recording problems; analyses were conducted on data from the remaining 18 women (mean age = 27.1 years, SD = 3.9), 19 men (mean age = 29.5 years, SD = 3.4), 20 boys (mean age = 15.1 years, SD = 1.2) and 20 girls (mean age = 15.2 years, SD = 1.6).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants were screened for any visual, neurological or psychological disorders prior to enrollment in the study. Data from 10 of the boys (selected to provide an age-matched sample with girls) were previously reported in a study with an all-male sample [28]. Data from 3 participants were discarded due to recording problems; analyses were conducted on data from the remaining 18 women (mean age = 27.1 years, SD = 3.9), 19 men (mean age = 29.5 years, SD = 3.4), 20 boys (mean age = 15.1 years, SD = 1.2) and 20 girls (mean age = 15.2 years, SD = 1.6).…”
Section: Methodsmentioning
confidence: 99%
“…However, neither of these two studies found age differences in the FRN in comparison to their adult group, nor did they find any sex-by-age interactions. It is possible that age-related differences were obscured because, in contrast to Hammerer et al [27] and Zottoli and Grose-Fifer [28], their adult samples included participants under the age of 21 years.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations